(untitled) (Global Journal of Science Frontier Research, 2015)
In this paper, we construct a dynamical system induced by the Adele ring ; based on the dynamical systems induced by -adic number fields ; for all primes : We study fundamental operator-theoretic and operator-algebraic properties of the corresponding crossed product operator algebra generated by such a dynamical system, via free probability.